Odious Debts and International Fair Trade - Dimitriu, Cristian (Daimon Revista Internacional de Filosofia, 2019)
I argue that one of the most important reasons why international trade has been unfair is that weaker parties in trading negotiations have been illegitimately forced to accept terms of trade that they would not otherwise accept under normal circumstances, and these terms of trade have been harmful for them. Odious debts are at the center of this kind of injustice. Odious debts are debts that are not binding for the citizens of a country, as they were incurred by illegitimate rulers in the name of all the citizens, but used for private purposes, such as personal benefit, or to oppress the population. Despite the fact that these debts are not binding—that is, that they should not be repaid—creditor countries have coerced debtor countries to repay them and, more importantly for the purposes of this article, they have taken advantage of the fact that countries are burdened with these debts by tailoring trade agreements in their favor. They have done so by telling debtor countries that, unless they trade under terms that creditor countries want; non-binding (i.e. odious) debts will be enforced. The resulting state of affairs is not simply a convenient one for creditor countries and an inconvenient one for debtor countries. It is also an immoral one.